The consumption expenditure response to unemployment: Evidence from Norwegian households - Andreas Fagereng; Helene Onshuus; Kjersti Næss Torstensen (Norges Bank, 2024)
We use detailed Norwegian administrative data to identify the income loss associated with the onset of unemployment and analyze the corresponding consumption expenditure response and the extent to which this response is related to household balance sheet components. Unemployment results in a significant, long-term decline in income. Consumption decreases by about one-third to one-half of the post-tax income reduction. This reduction is less pronounced for liquid households and more for indebted ones. Although both debt and liquidity impact consumption patterns, debt has a predominant influence, especially for households holding substantial amounts of both. These households, despite their liquidity, also reduce their consumption upon unemployment, while consistently dedicating a substantial part of their disposable income to mortgage commitments. Furthermore, we investigate heterogeneity along other important margins such as family composition and child age. Finally, the patterns of our spending responses (measured as the marginal propensity to consume, the MPC) are found to be more pronounced during recessions.
hdl:11250/3172760
Keywords: D12; E21; E24; 330; unemployment; household finance; consumption expenditure; consumption smoothing; household heterogeneity